Real Time Investments with Adequate Portfolio Theory - Alina Kvietkauskienė (Entrepreneurial Business and Economics Review)
The objective of this paper is to identify investment decision makingschemes using the adequate portfolio model. This approach can be employed to project investment in stocks, using the opportunities offered by the markets and investor intelligence. It was decided to use adequate portfolio theory for investment decision making, simulation of financial markets, and optimisation of utility function.Â The main conclusion of article suggests investigating return on individual portfolio level. Real investment is a way to make sure of the soundness of applicable strategies.